Disney's dinozauras - Šidiškytė, J. (Jurga); Edward Valauskas Collection of Dinosauriana (Vilnius : Egmont Lietuva, 2000)
Lithuanian translation of: Dinosaur.
Gift of Edward Valauskas.
From the Edward Valauskas Collection of Dinosauriana.
Keywords: Dinosaurs -- Juvenile fiction; Lemurs -- Juvenile fiction; Quakers -- Juvenile fiction